Cellular mechanisms for cargo delivery and polarity maintenance at different polar domains in plant cells - Łangowski, Łukasz; Wabnik, Krzysztof; Li, Hongjiang; Vanneste, Steffen; Naramoto, Satoshi; Tanaka, Hirokazu; Friml, Jiří (Cell discovery, 2016)
The asymmetric localization of proteins in the plasma membrane domains of eukaryotic cells is a fundamental manifestation of cell polarity that is central to multicellular organization and developmental patterning. In plants, the mechanisms underlying the polar localization of cargo proteins are still largely unknown and appear to be fundamentally distinct from those operating in mammals. Here, we present a systematic, quantitative comparative analysis of the polar delivery and subcellular localization of proteins that characterize distinct polar plasma membrane domains in plant cells. The combination of microscopic analyses and computational modeling revealed a mechanistic framework common to diverse polar cargos and underlying the establishment and maintenance of apical, basal, and lateral polar domains in plant cells. This mechanism depends on the polar secretion, constitutive endocytic recycling, and restricted lateral diffusion of cargos within the plasma membrane. Moreover, our observations suggest that polar cargo distribution involves the individual protein potential to form clusters within the plasma membrane and interact with the extracellular matrix. Our observations provide insights into the shared cellular mechanisms of polar cargo delivery and polarity maintenance in plant cells.
Keywords: polar recycling; protein dynamics modeling; polar secretion; protein clustering; protein trafficking; lateral diffusion